Cultural influences on the fertility behaviour of first- and second-generation immigrants in Germany - Holger Stichnoth; Mustafa Yeter (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Based on a 1% sample of the German population, we study how fertility rates in the country of origin-a proxy for cultural imprint-influence the fertility outcomes of first- and second-generation female immigrants. We use both total fertility rates in the year of migration and a new measure of completed cohort fertility rates in the countries of origin as well as direct survey measures of fertility norms. Our large data set allows us to focus on a relatively narrow range for age at migration and to estimate models that rely on within-country variation only, leading to more credible identification. We find a statistically significant, sizeable and robust effect of country-of-origin fertility rates on fertility outcomes. The effect is strongest for the first generation and becomes weaker, though still statistically significant, for 'generation 1.5' (migrants arriving as children) and the second generation. It is stronger for women with low education and for women who live with a partner from the same country of origin.
urn:nbn:de:bsz:180-madoc-333282
Keywords: J13; J15; J16; 330; Immigration; fertility; assimilation; intergenerational transmission; Germany